EFISIENSI EFISIENSI SISTEM INVENTORI PADA PERUSAHAAN PERKEBUNAN KELAPA SAWIT PT AGRO ABADI - Akhmad Zulkifli (STMIK Hang Tuah Pekanbaru, 2018)
Agro Abadi is a palm oil plantation company located in Buluh Nipis village, Siak Hulu District, Kampar Regency, Riau, Indonesia. The current inventory system called The GL Program which is still desktop based and its performance is less efficient. The expenditure of goods from warehouses and bookkeeping using the manual journal (handwritten), which sometimes made a mismatch result between stock data and the actual stock of goods, in addition to stock checking takes a relatively long time. The report display of this program is incomplete because of unable to display per sub-item name, and there is no price info of goods displayed. This program has still many tables that are not needed and have nothing to do with the system running. Keyword : Inventory, PT. Agro Abadi